Socio-Economic Problems of Agricultural Laborers in Punjab (Pakistan) (Journal of Asian Development Studies, 2024)
The development of the agriculture sector is one of the most imperative factors for fulfilling basic human needs, alleviating poverty, boosting shared prosperity, and becoming a significant contributor to national development for most developing countries. Over one billion of the world's labour force is engaged directly and indirectly in this sector, one-third of the world's workforce. Unfortunately, the laborersworking in the agriculture sector face multidimensional socioeconomic problems such as poor livelihood conditions, meagre employment circumstances, long working hours, fewer rewards, unavailability of basic safety facilities, remuneration and pitiable nutrition, among others. To understand the contributing factors responsible for socioeconomic problems, this study was conducted in three divisions of Punjab province: Gujranwala, Faisalabad, and Dera Ghazi Khan. For this purpose, a multistage simple random sampling procedure was applied to approach the participants. The interview schedule was used as a tool for data collection and validated through pilot testing. The study's findings revealed that the laborers’employment conditions could have been more conducive while agricultural laborerswere receivinglesser wages. The agricultural laborershave to face many health hazards. In contrast, the majority of the laborerswere exploited only due to their illiteracy and ignorance about Government policies and laws related to them. Many participants reported chronic socioeconomic problems significantly associated with their working environment, amenities and available facilities.